Arsenic phytovolatilization and epigenetic modifications in Arundo donax L. assisted by a PGPR consortium. (July 2020) - Guarino, Francesco; Miranda, Antonio; Castiglione, Stefano; Cicatelli, Angela
Abstract: Arsenic-(As) pollution is an increasing threat across the globe and it is reaching harmful values in several areas of the world. In this perspective, we assayed bio-phyto-remediation technology using Arundo donax L., assisted by Plant Growth Promoting Bacteria (PGPB) consortium (BC) constituted of two strains of Stenotrophomonas maltophilia sp. and one of Agrobacterium sp.; furthermore, we assayed the epigenetic response to As pollution. The three bacterial strains initially evaluated for their As tolerance, revealed different resistance to both forms of As[As(III) and As(V)] however at concentration greater than those foreseen in the phytoremediation experiment (2.0, 10.0, 20.0 mgL −1 of NaAsO2 ). At the end of the trial plant biomass and As concentration were measured. Plants did not show any visible signs of toxicity, rather the leaf and stem biomass slightly increased in the presence of As and/or PGPBs; moreover, although the Bioaccumulation Factor was double in the presence of BC, the absolute values of As accumulation in the Arundo plants were very low, both in the presence or absence of BC and only detectable in the presence of the highest As dose (20 mgL −1 As). In this case, regardless the presence of PGPB, ≈25% of As remained in the sand and ≈0.15% was accumulated in the plant, whilst the remaining 75% was volatilized by transpiration. Finally, the methylation sensitive amplified polymorphisms (MSAP) of leaves were analyzed in order to investigate their epigenetic response to As and/or BC. Our results suggest that epigenetic modifications are involved in stress response and As detoxification. Highlights: The PGBPs used in this study are differentially tolerant to As(V) and As(III). The two S. maltophilia are resistant up to 165.00 mg L −1 of As(III), while the Agrobacterium up to 80.00 mg L −1 of As(III). Arundo donax takes up and volatilizes As(III). The percentage of As removal efficiency in Arundo plants was higher than 50%. DNA methylation mechanism is involved in As stress response of Arundo.